Phytochemical Standardization of Oleo Resin of Shorea robusta Gaertn (Dipterocarpaceae) with modern analytical technique - Mohd Abdul Rasheed Naikodi; Kommu Nagaiah; M.A. Waheed (International Journal of Phytomedicine, 2012)
More than 70% of India’s 1.1 billion populations still use non-allopathic systems of medicine like Ayurveda, Unani, Homeopathy and other systems. The global knowledge about Unani and Indian herbals will hopefully be enhanced by information on the evidence-base of these medicinal plants. Resin of Shorea robusta Gaertn known as “Raal” in Unani; Shala in Ayurvedic System belonging to Dipterocarpaceae family plays a foremost role in the Unani system of medicine. It is abundantly available in different parts of Eastern Ghats of Southern Peninsular India and has been widely used in indigenous system for the preparation of different formulations used in the treatment of many skin diseases mainly allergies; diarrhea, dysentery, astringent and as an ingredient in ointments. Due to its therapeutic potentials and vital medicinal properties and also usage of drug in most of the common ailments, lead us to standardize the drug according to WHO guidelines. Phytochemical and physico-chemical studies, macroscopic and microscopic properties of resin were carried out. The main aspects included in the study are organoleptic characters, physico-chemical constants, fluorescence analysis of powdered drug and extracts, TLC profile and Heavy metal analysis, which provide information, which are widely accepted in the quality assessment of herbal drugs and to lay down the standard for the genuine drug. Phytochemical screening, isolation of chemical constituents will help in future to study the pharmacological properties.